2014
DOI: 10.4236/ajac.2014.59062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Thermal Plasma Modified NiAl Layered Double Hydroxides on the Removal of Fluoride from Aqueous Solution

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The previous studies have shown that one of the disadvantages of PCL scaffold is its intrinsic hydrophobic property which decreases cell adhesion on the scaffold surface and as a result, reduces the cell-scaffold interaction (Lu et al 2014 ). Increasing cellular interactions with scaffolds is an important solution for tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have shown that one of the disadvantages of PCL scaffold is its intrinsic hydrophobic property which decreases cell adhesion on the scaffold surface and as a result, reduces the cell-scaffold interaction (Lu et al 2014 ). Increasing cellular interactions with scaffolds is an important solution for tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
“…(32) (33) where, b T (J mol −1 ) is Temkin constant which is related to the heat of sorption and K T (L mg −1 ) is Temkin isotherm constant, T (K) the absolute temperature, R is the gas constant 8.31 J mol -1 K -1 .…”
Section: Adsorption Isotherm Modelsmentioning
confidence: 99%
“…In the case of Ni/Al-LDH, it has been reported as highly efficient in the adsorption of metals (Au, Cd, Cu, Pb, Se), 28,32 anions (F -, IO 3 -) 33,34 and organic compounds. [24][25][26]29,35,36 Ni-based LDHs in the energy storage and conversion field are still limited by their intrinsically poor conductivity, aggregation, limited active sites and stability.…”
Section: Introductionmentioning
confidence: 99%
“…LDHs have attracted a lot of attention as F adsorbents in the recent past. Lu et al [148] assessed F removal based on NiAl layered double hydroxides (NiAl-LDHs) and reported a low equilibrium F concentration of just 0.2388 mg/L in the treated water. Sadik et al [149] also reported high F removal rates of 99.2% for calcined LDHs synthesized from seawater (LDHsw).…”
Section: Layer Double Hydroxidesmentioning
confidence: 99%